Peranan Badan Perencanaan Pembangunan Daerah dalam Penyusunan Rencana Kerja Pembangunan Daerah Kabupaten Simeulue 2022 - Leli Putri Ansari leli; Satris Ali Sandra satris (Publikasi Indonesia, 2022)
The Regional Development Work Plan (RKPD) is the elaboration of the Regional Medium-Term Development (RPJMD)for aperiod of 1(one) year, which contains the design of the regional economic framework. Priority for regional development is the work plan and its funding, both those implemented directly by encouraging community particion. Referringto the RKPD then becomes a guideline for the preparation of the Regional Revenue and (RAPBD). This study aims to analyze the role of Bappeda in the preparation of the Simeulue District Regional Development Work plan (RKPD) in 2022 and the inhibiting factors. This research is a descriptive qualitative research using primary data where the data is obtained from interviews with informants, and the authors researched at the Regional Development planning Agency (Bappeda) of Simeulue Regency which is located on Jalan Teuku Diujung Air Cold Village, East Simeulue District, Simeulue Regency. Based on the results of the study, it shows that the Bappeda of Simeulue Regency in its role as the Preparation of the Simeulue Regency Regional Development work Plan (RKPD) for 2022 has not been carried out very well, because it is influenced by inhibiting factors such as the slow submission of the required data, the lack of Local Origin Opinions (PAD), and lack of Transfers to Regional Funds (TKDD).